Sistem Pakar Diagnosa Kerusakan Pada Mobil Toyota Innova Dengan Metode Backward Chaining Dan Certainity Factor - Jason Aldrian; Djoni Haryadi Setiabudi (Jurnal Infra, 2022)
Car is one of the transportation that used commonly by human. Toyota Innova is one of the most favorite family car in Indonesia. Toyota Innova has a lot of type and variations that need to be handled. There is Manual transmission and Automatic Transmission. Damage to car cannot be taken so easily, Not only big damage that can cause breakdown. But small problems or damage to car can cause breakdown or failure, Small damage is need to handled too as important as big damage so it would not become fatal damage. Diagnostics on the car for people who don't really understand cars can be really confusing and the number of repair shops that are not honest in diagnosing damage will cause losses for car owners. If in an urgent situation this system can be used to find out what damage has occurred and make it possible to check and repair the damage to the car that occurred. This Expert System for Damage Diagnosis on Toyota Innova is using Forward Chaining and Certainty Factor as it’s method. Backward Chaining on this expert system is for collecting symptoms and facts that come into some conclusions so users don't have to answer all the questions. And the usage of Certainty Factor on this system to show the percentage of system belief on the diagnosis. So user can trust on the result of diagnose. The results of tests that have been carried out 20 times from tests by experts, There is 19 results that suitable with expert opinion. There is 1 result that is not suitable with expert opinion because of the inaccuracy of the CF percentage. As of that result user can still look for the solution in the damage encyclopedia. In this test, the percentage for detecting damage to the Toyota Innova car using the Backward Chaining method and Certainty Factor is 95% in accordance with expert opinion.